God’s World Is Not an Animal Farm – Or Is It?: The Catachrestic Translation of Gender Equality in African Pentecostalism - Van Klinken, A. S. (Religion & gender, 2013)
Building on scholarly debates on Pentecostalism, gender and modernity in Africa, this article engages a postcolonial perspective to explore and discuss the ambivalent, even paradoxical nature of African Pentecostal gender discourse. It analyses the conceptualization of gender equality, in particular the attempt to reconcile the notions of ‘male-female equality’ and ‘male headship’, in a sermon series delivered by a prominent Zambian Pentecostal pastor, and argues that the appropriation and interruption of Western notions of gender equality in these sermons can be interpreted, in the words of Homi Bhabha, as a catachrestic postcolonial translation of modernity. Hence, the article critically discusses the Western ethnocentrism in some scholarly debates on gender and Pentecostalism in Africa, and points to some of the fundamental questions that Pentecostalism and its ambivalent gender discourse pose to gender-critical scholarship in the study of religion.